1978
DOI: 10.1002/jcp.1040940104
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of colony stimulating activity from large batches of human urine and production of antisera against it

Abstract: In vitro induction of myelopoetic colonies from mouse bone marrow has been used for measurement of leucopoetic colony stimulating activity (CSA) isolated from large batches of human urine. After high flow dialysis in artificial kidneys and immediate adsorption to DEAE-Cellulose, followed by purification on Con A-Sepharose, treatment with insoluble Papain and gelfiltration on Sephadex G 100, enrichment of CSA was about 6,000-fold. An important step of the enrichment procedure was the separation from a CSA-inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1979
1979
1987
1987

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…According to Metcalf and Stanley (19691, the urinary CSF concentration varies over a range of 0-300 unitdm1 depending upon the total daily urine volume, while the mean was about 60 units/ml. Other workers also reported the urinary CSF concentration to be about 9 units/ml (Motoyoshi et al, 1978), 30 units/ml (Laukel et al, 1978), or 32 unitdm1 (Ishii et al, 198213). The peritoneal CSF concentration observed in the present study seems to be nearly comparable with the concentration of CSF in normal human urine.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Metcalf and Stanley (19691, the urinary CSF concentration varies over a range of 0-300 unitdm1 depending upon the total daily urine volume, while the mean was about 60 units/ml. Other workers also reported the urinary CSF concentration to be about 9 units/ml (Motoyoshi et al, 1978), 30 units/ml (Laukel et al, 1978), or 32 unitdm1 (Ishii et al, 198213). The peritoneal CSF concentration observed in the present study seems to be nearly comparable with the concentration of CSF in normal human urine.…”
Section: Discussionmentioning
confidence: 97%
“…It is also our aim to compare the peritoneal CSF with the CSF from normal human urine. The urinary CSF has been considerably been purified and characterized by many workers (Stanley et al, 1975;Laukel et al, 1978;Motoyoshi et al, 1978). The comparison of the peritoneal and urinary CSFs will disclose the difference between the freshly produced CSF and the CSF excreted ultimately in the urine.…”
mentioning
confidence: 99%
“…The factor is produced in various tissues as well as by various cultured cells, and displays an apparent heterogeneity of molecular properties principally due to its nature as a sialoglycoprotein (Stanley et al, 1971;Ayusawa et al, 1979;Tsuneoka and Shikita, 1980a). On the other hand, CSFs produced by various organs of endotoxin-treated mice are universally similar to each other in that they all produce an active principle of 23,000 daltons upon desialylation and gel-filtration chromatography in the presence of 6 M guanidine (Nicola et al, 1979), whereas there is another subclass CSF of higher molecular weight, such as those obtained from mouse L-cell conditioned medium (Stan-ley and Heard, 1977;Tsuneoka and Shikita, 1977;Waheed and Shadduck, 1979;Tsuneoka and Shikita, 1980b) or from human urine (Stanley et al, 1975;Laukel et al, 1978). Recently, we have reported that two types of CSF are inducible in the culture of mouse spleen cells in response to either endotoxin or x-rays (Onoda et al, 1980).…”
mentioning
confidence: 97%
“…This supposed dual action of CSA would there fore be similar to that of erythropoietin in stimulating erythropoiesis and hemoglobin synthesis as well. Our current knowledge on the regulation of neutrophil and macrophage production by CSA almost entirely originates from cultures of progenitor cells in semisolid agar or methylcellulose [4,12,14,20].…”
Section: Introductionmentioning
confidence: 99%